Oxysterol-EBI2 signaling in immune regulation and viral infection - Daugvilaite, Viktorija (BlackWell Publishing Ltd, 2014)
The seven transmembrane G protein-coupled receptor Epstein-Barr virus (EBV) induced gene 2 (EBI2; also known as GPR183) was identified in 1993 on the basis of its substantial upregulation in EBV-infected cells. It is primarily expressed in lymphoid cells; most abundantly in B cells. EBI2 is central for the positioning of B cells within the lymphoid organs, a process that is regulated in part by a chemotactic gradient formed by the endogenous lipid agonists, and in part by a fine-tuned regulation of EBI2 cell surface expression. The most potent endogenous EBI2 agonist is 7α, 25-dihydroxyxcholesterol (7α,25-OHC), yet many structurally related oxysterols can bind to an EBI2 pocket that is defined by the upper parts of the transmembrane helices and extracellular receptor regions. EBI2 signals via Gαi, as well as via G protein-independent pathways like β-arrestin recruitment. The concerted action of these pathways leads to cell migration. By genetically interfering with its up- and downregulation, EBI2 was also recently shown to induce cell proliferation, an action that could be inhibited by small molecule antagonists. Here, we focus on the oxysterol–EBI2 axis in immune control, including its role in the EBV life cycle. We also summarize the structural and functional properties of EBI2 interaction with oxysterol agonists and small molecule antagonists and discuss EBI2 as therapeutic target for diseases of the immune system.